Dilemmas appropriate for qualitative research in the field of development cooperation: a delicate question - Pulido Fuentes, Montserrat (Acta Bioethica, 2017)
This article analyzes the ethical dilemmas which the authoress had to face during the accomplishment of the anthropologic investigation for what it would be his doctoral thesis, in the frame of a project of cooperation the development in the area of the health. There signs a process of integration, of comprehension and of understanding in the own investigator, taking up office, sometimes resolving, and even understanding them as part of the same process of investigation, therefore it appropriates of them, internalizes them. The dilemmas that they present in the fieldwork are valued as part of this type of initiation works, contrasting with investigations and consolidated investigators and, observing that these difficulties appear in different areas and of multiple forms, is considered to be necessary the boarding of this type of questions by methodological rigor, as well as the consequent analysis, estimating them as something intrinsically to the investigations realized with others and that sustain interventions in health. The emphasis is tried to put in this aspect, in spite of being a central topic the ethics, when we speak about investigations with subjects and social groups, since one dedicates him a little time in the formation and investigative practice.